Retrabalhos realizados em imóveis residenciais recém entregues na cidade de Manaus – AM por empresa especializada e o seu custo em relação ao de aquisição - Morais, Laine Gabriela Machado (Brasil, 2022)
Civil construction is one of the branches that most contribute to the country's economy. In addition to bringing a financial return to the government from taxes included in the construction costs, it also enables several jobs to fulfill its workforce, contributing directly to the country's GDP. However, an industry that is still very “artisanal”, in the sense of needing, in many aspects, human labor in the design, execution and inspection, naturally becomes passive to many errors and unforeseen events during its execution. The construction companies, in order to reduce their costs and launch values of the sale of properties, invest less and less in finishing materials, as they consider that the new resident is the one who will have to choose, according to the interior project, the best way that this will be done. In this work the focus is to talk about the renovation of newly acquired properties and what will be the costs for their adaptations. The study was carried out from the services performed by a company specialized in this type of service.